A CASE OF HYPERTRIGLYCERIDEMIA-INDUCEDSEVERE ACUTE PANCREATITIS - WHAT ELSE CAN BE DONE? - G. Minkov; E. Dimitrov; E. Enchev; Kr. Halacheva; F. Hadjipetkov; Iv. Dimitrov; St. Nikolov; A. Petrov; Y. Yovtchev (Trakia Journal of Sciences)
Purpose: Acute pancreatitis (AP) often presents as complex diagnostic and management challenge to physicians, surgeons and radiologists caring for patients with the disease. Methods: In this article we present a case of a young woman with AP induced by hypertriglyceridemia (HTGP) that runs on the background of diabetic ketoacidosis with unusual clinical picture and normal amylase. Results and Conclusions: HTGP involves young people. Most of the cases can be presented with normal values of amylase and lipase, but the possibility of severe complications and the lack of specific therapies determine the need of early recognition. HTGP may need specific behaviour additional of generally accepted guidelines for the treatment of AP.